Basic communication skill drill in microteching context to improve the teching skills of civil engineering and planning education students, faculty of engineering, Yogyakarta State University. (May 2019) - Suparman,; Slamet,; Pratama, GNIP
Abstract: This study aims to investigate whether the drill method (verbal and non-verbal communication skill drill) is able to improve the basic teaching skills in microteaching context. This is classroom action research. The population consisted of students majoring in Civil Engineering and Planning Education Department, Faculty of Engineering, Yogyakarta State University who were taking microteaching practice course. The sample of the study was class A1 consisted of 11 students. The study was conducted in three cycles. Cycle 1 contained basic verbal communication, cycle 2 encompassed basic non-verbal communication, and cycle 3 covered both basic verbal and non-verbal communication types. Observation and skills assessment sheets were employed. The qualitative descriptive and descriptive statistics methods were then used to analyze the data.The results show that: (1) basic verbal communication skill drill in microteaching practices improves student teachers' basic microteaching skills and (2) basic non-verbal communication skill drill in microteaching practices improve student teachers' basic microteaching skills.